واقع الهندرة فى مکتبات الکلیات بجامعة سوهاج دراسة استکشافیة تخطیطیة - د. ممدوح على محمود (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aimed at exploring the state of the art of Businessprocess re-engineering in Sohag University (SU) college libraries. Toachieve the objectives of the study, a questionnaire was developed forstakeholders in SU college libraries, in addition to personal interviews andfield visits.A sample of 132 librarians represented the population of the study(79% of the population). Results showed the following: there is a sufficientdegree of awareness among librarians of the concepts of administrativedevelopment. However, the concept of managerial operationsreengineering was alien to them. There was absence of strategic planning,librarian trainings, managerial bodies and regulating bylaws in SU libraries.Results showed also some obstacles in the way of applying managerialoperations reengineering among them is the low level in using IT.The study suggested some recommendations. Amongst them arethe following: reinforcing the concept of managerial operationsreengineering, developing librarians' capacities, determining a clearmanagerial policy, and using IT skills in designing all managerialoperations reengineering